The role of constitutional court in the process of consolidating democracy in Indonesia: analysis of judicial review relating to election matters - Mokhtar, Khairil Azmin; Satriawan, Iwan (2014)
The establishment of Constitutional Court in 2003 has given a new impetus to democracy in the constitutional system of Indonesia. After more than a decade of its existence there is a need to ascertain the role of the Court in the process of consolidating democracy and determine, if any, of its impact to the country and effect on democracy. The primary question is whether the Constitutional Court has managed to achieve expectation of the people and fulfil its democratic role in upholding the constitutional principles and institutionalizing democratic values in Indonesia? In trying to answer the question this article initially discusses the theoretical aspect and political background of the emergence and development of constitutional court globally, together with discussion on the meaning, significance and relevance of democracy, democratic consolidation, judicial review and election. The ensuing discussion is constitutional and political setting and backdrop relating to the emergence and establishment of the Constitutional Court in Indonesia. The article then proceeds to examine whether the Constitutional Court, through it powers and decisions relating to election matters, have influenced the agenda of strengthening democratic consolidation in the country. This study concludes that the emergence of the Constitutional Court as an organ for constitutional adjudication mechanism is the result of development of modern idea of democratic government which is based on the rule of law, doctrine of separation of powers, and the protection of fundamental rights of citizens. The findings in this article pointed to the conclusion that the Constitutional Court, through its powers and decisions, improves the quality of legislation and elections. The improvements have positive consequences to democracy because it strengthen democratic values, protects fundamental rights of citizen, and conducts checks and balances mechanism among state institutions.